2020
DOI: 10.1155/2020/7571838
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Assessment in Diabetic Patients Using a Validated Tool in a Patient Population Visiting a Tertiary Care Center in Bhubaneswar, Odisha, India

Abstract: Odisha has 4.2 million diabetic patients against the country’s 70 million with an urban prevalence of nearly 15.4%. Diabetes is affecting younger age groups, thus having a crucial impact on quality of life of the affected. A qualitative endeavour was attempted at the diabetic clinic of a tertiary care set up in the capital city of Bhubaneswar to create a diabetic surveillance data assembly, wherein subjects above 18 years of age and newly diagnosed or on follow-up, after obtaining informed consent, were made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…13,14 Some other studies also reported similar findings, however, they used different instruments other than WHQOL BREF. 12,15 It was observed that the physical health domain was the most affected domain followed by the environmental domain, at 55.02±7.70 and 57.81±19.64 respectively, supported by a study conducted in Nepal Mishra et al reported similar findings in their studies for physical quality of life domain 50.7±11.8. 13,16 With regard to self-care activities, it was reported that even though a high percentage of individuals practiced healthy diet (65.3%), including 5 or more fruits or vegetables (67.3%) and spacing the carbohydrates well (72.6%), when it comes to physical exercise (22%), blood glucose monitoring (0.7%) and foot care (33.3%) they are falling behind.…”
Section: Discussionsupporting
confidence: 55%
“…13,14 Some other studies also reported similar findings, however, they used different instruments other than WHQOL BREF. 12,15 It was observed that the physical health domain was the most affected domain followed by the environmental domain, at 55.02±7.70 and 57.81±19.64 respectively, supported by a study conducted in Nepal Mishra et al reported similar findings in their studies for physical quality of life domain 50.7±11.8. 13,16 With regard to self-care activities, it was reported that even though a high percentage of individuals practiced healthy diet (65.3%), including 5 or more fruits or vegetables (67.3%) and spacing the carbohydrates well (72.6%), when it comes to physical exercise (22%), blood glucose monitoring (0.7%) and foot care (33.3%) they are falling behind.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, in a study conducted by Meher D et al in Bhubaneswar among 400 diabetic subjects, in the year 2020, it was found that the patients with age over 50 years had poor quality of life. 18 However, in a study conducted by Timar R et al in 2016 in Romania, no significant association was found between quality of life and age of diabetic subjects. 19 Overall quality of life and general health score was significantly lower in illiterate subjects (26.97) than literate subjects in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…The initial objective of the study which is published,[ 7 ] of validating the QOLID tool in eastern India population, 10 samples per item were needed for validation of questionnaire[ 8 9 ] for 34 items in the scale, thus minimum sample of 340 subjects. For this study, to assess the effect of the pandemic, we had a ready sample size of 599 respondents, stratified for 343 respondents in pre COVID and 256 in COVID period.…”
Section: Methodsmentioning
confidence: 99%
“…All individual standardized domain scores were then added and divided by 8 (number of domain) to obtain an overall score for the study. [ 7 ]…”
Section: Methodsmentioning
confidence: 99%